2018
DOI: 10.1016/j.euroneuro.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Translating molecular advances in Down syndrome and Fragile X syndrome into therapies

Abstract: Ongoing treatments for genetic developmental disorders of the central nervous system are mostly symptomatic and do not correct the genetic cause. Recent identification of common mechanisms between diseases has suggested that new therapeutic targets could be applied across intellectual disabilities with potential disease-modifying properties. The European Down syndrome and other genetic developmental disorders (DSG2D) network joined basic and clinical scientists to foster this research and carry out clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 141 publications
0
14
0
Order By: Relevance
“…These factors could consist of missing close contacts between pyramidal neurons and other cell types, such interneurons, astrocytes or other glial cells. The study of trisomic neurons developing within brain organoids (Faundez et al, 2018) may represent a very interesting possibility to further address this phenomenon and to unravel its molecular details.…”
Section: Discussionmentioning
confidence: 99%
“…These factors could consist of missing close contacts between pyramidal neurons and other cell types, such interneurons, astrocytes or other glial cells. The study of trisomic neurons developing within brain organoids (Faundez et al, 2018) may represent a very interesting possibility to further address this phenomenon and to unravel its molecular details.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been reported that lithium, a drug approved for human use as mood stabilizer, can extend lifespan in animal models through the inhibition of GSK‐3 and activation of NRF2 (Castillo‐Quan et al, ); therefore, it could be considered an additional approach to delay the aging process. Interestingly, a number of studies have examined the effects of chronic lithium administration on adult neurogenesis in the Ts65Dn mouse model of DS (Bianchi, Ciani, Contestabile, Guidi, & Bartesaghi, ; Contestabile et al, ; Faundez et al, ; Guidi et al, ). These studies indicated that the administration of lithium can restore the neurogenesis in adulthood thus rescuing the synaptic plasticity of newborn neurons, that in turn leads to the recovery of behavioral performance in fear conditioning, object location, and novel object recognition tests (Contestabile et al, ), as well as olfactory functions (Guidi et al, ).…”
Section: How To Face the Cognitive Deterioration Of Ds Persons?mentioning
confidence: 99%
“…Considering that mouse or other animal models work only provides evidence of treatment adequacy but not of specific outcomes, the possibility of skipping altogether in vivo model testing has been raised. Instead, in vitro evaluation of iPSC-derived neural cells offers the opportunity of testing directly cells from individuals with FXS and showing correction of cellular abnormalities, data that not only could be used for demonstrating treatment effectiveness but also subject selection [6]. However, this intriguing new approach does not test extension of cellular changes to neurobehavioral outcomes and will need to be systematically compared with current animal model standards prior to its full implementation [2].…”
Section: Preclinical Developmentmentioning
confidence: 99%